Study of the Chemical Composition, Amino Acid, Flavonoids and Vitamin C of Moringaoliefera Leaves Extract Grown in AL-Ramadi- Iraq - Hind YounisKhalaf; Abid Ali Thaker; Mahdi Salih Shalal (Indian Journal of Forensic Medicine & Toxicology, 2021)
This study was conducted to reveal the chemical components, amino acids, flavonoids and vitamin C ofthe aqueous leaves extract of Moringaoliefera plant grown in AL-Ramadi city in Iraq, because these herbalplants have medicinal and nutritional importance.material and method.The leaves were collected fromMoringaOleifera tree grown in the home garden, aqueous extract was prepared and GC-MS analysis, aminoacid diagnostics, flavonoids diagnosis and vitamin C analysis were performed. Results sixteen chemicalconstituents were identified in the leaf aqueous extract; The most important of these compounds Decanoicacid(1.14%),17- Octadecynoic acid (29.24%), (7.51%). 12 types of essential and non-essential aminoacids were diagnosed.Extraction of phenolic compound showed presence of quercetine(245.7 ppm) andkaemferal(299.6 ppm). Vitamin C content in fresh samples of leaves of M. olifera were determined by theHPLC method was (250.2 ppm).